2017
DOI: 10.1209/0295-5075/119/34002
|View full text |Cite
|
Sign up to set email alerts
|

Soft X-ray generation in cascade SASE FEL with two-frequency undulator

Abstract: The generation of soft X-ray radiation in cascade self-amplified spontaneous emission free electron laser (SASE FEL) using harmonics of a two-frequency undulator is studied. An advanced phenomenological model of SASE FEL, accounting for the properties of the undulator and of the electron beam, including major losses, is employed. The account for the beam energy spread, divergence and diffraction is harmonic dependent, which is a step forward from the previous models and phenomenological approach, which conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 34 publications
(27 reference statements)
0
8
0
3
Order By: Relevance
“…Experiments on the harmonic generation in HGHG were performed at FERMI facility; [36] it has been using this regime during the last 10 years; the studies showed the possibility to generate harmonic radiation in HGHG with the last undulator. [41] Studies [39][40][41][42][43][44] demonstrate that using HGHG, UV-and X-ray radiation can be produced in more compact devices, as compared with FELs where the fundamental tone is generated at the same wavelength; the typical beam energies in the FELs, where the fundamental wavelengths are 𝜆 < 1 nm are E ≈ 10 GeV. Generation of harmonics was used also in the FLASH FEL, [45,46] whose undulators have variable deflection parameter k. This allowed studies of the harmonic radiation in a FEL with the harmonic lasing self-seed (HLSS), where the first FEL undulators operate in SASE regime and their harmonic is amplified in the last sections.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments on the harmonic generation in HGHG were performed at FERMI facility; [36] it has been using this regime during the last 10 years; the studies showed the possibility to generate harmonic radiation in HGHG with the last undulator. [41] Studies [39][40][41][42][43][44] demonstrate that using HGHG, UV-and X-ray radiation can be produced in more compact devices, as compared with FELs where the fundamental tone is generated at the same wavelength; the typical beam energies in the FELs, where the fundamental wavelengths are 𝜆 < 1 nm are E ≈ 10 GeV. Generation of harmonics was used also in the FLASH FEL, [45,46] whose undulators have variable deflection parameter k. This allowed studies of the harmonic radiation in a FEL with the harmonic lasing self-seed (HLSS), where the first FEL undulators operate in SASE regime and their harmonic is amplified in the last sections.…”
Section: Introductionmentioning
confidence: 99%
“…Наряду с этим в ЛСЭ также используют эхо нескольких затравочных лазеров, которые последовательно модулируют энергию электронного банча [15]; этот принцип реализован, например, в [16,17]. Возможен случай, когда гармоника в ондуляторе не излучается, но группировка электронов на ее длине волны создает эквивалентную мощность для усиления в следующем ондуляторе, настроенном в резонанс [18,19]; возможно также использование нескольких каскадов для умножения гармоник [20][21][22]. Применение монохроматоров или иная фильтрация излучения между каскадами ЛСЭ, настроенных на гармоники друг друга, позволяет получить от первых ондуляторов в режиме SASE затравочное лазерное излучение для последующих каскадов ЛСЭ (harmonic lasing selfseed, HLSS); этот принцип реализован, например, в ЛСЭ FLASH2 с изменяемым параметром дипольности k ондуляторов [23,24].…”
Section: к жуковскийunclassified
“…The latter is based on the Pierce parameter ρ [45][46][47][48][49][50], and it significantly develops the first approach in [51][52][53], applied with some modifications in [54][55][56][57][58][59][60]. The present formulation in contrast with [51][52][53] describes all losses separately for each FEL harmonic; it also includes the gradual dual-stage saturation and reproduces the oscillations of the saturated power, differently from that in [54][55][56][57][58][59][60]. Moreover, formulae (4)-( 7), ( 22), ( 23) above in Section 2 in the limiting cases of the planar 2-frequency undulator correct the misprinted results in [54][55][56][57][58][59][60].…”
Section: Analysis Of the Harmonic Generation In Some Fel Experimentsmentioning
confidence: 99%